Possibilities of a virtual сolonosсopy in diagnostics of an adhesive disease - A. K. Leisle; A. V. Ushakov; V. D. Zawadovskaya (Бюллетень сибирской медицины, 2012)
Results of carrying out a technique of a virtual colonoscopy to 15 patients with clinic of an adhesive illness with the instruction on features and comparison among themselves various modes of visualization of the program module of a virtual colonoscopy are described. 5 clinical cases with an illustration of the revealed changes are given.